2019
DOI: 10.1088/1361-665x/ab1ce6
|View full text |Cite
|
Sign up to set email alerts
|

Improving the seismic performance of post-tensioned self-centering connections using SMA angles or end plates with SMA bolts

Abstract: Cyclic performance of self-centering post-tensioned (PT) steel beam-column connections has been investigated numerically by introducing stiffened angle connection, shape memory alloy (SMA) angle connection and SMA bolted end plate connection. Results show that stiffened angle connection can significantly improve the seismic performance in terms of moment capacity (up to 40% increase), post-decompression stiffness (up to 58% increase) and energy dissipation capacity (up to 67% increase) compared to the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The distance between the center of the first bolt row and compression center is defined as h bo . The modified individual equivalent stiffness in the same row can be obtained by equations (15)- (17).…”
Section: Assessment Of Initial Rotational Stiffness By Component Methodsmentioning
confidence: 99%
“…The distance between the center of the first bolt row and compression center is defined as h bo . The modified individual equivalent stiffness in the same row can be obtained by equations (15)- (17).…”
Section: Assessment Of Initial Rotational Stiffness By Component Methodsmentioning
confidence: 99%
“…To prevent significant plastic deformations from occurring in ED members, the SMA angles were proposed and applied to self-centering connections by Chowdhury et al [47]. e test results showed that the SMA (FeNCATB alloy) angles could reduce residual displacement of ED elements in which the recover strain could reach 13.5%.…”
Section: Connections Using Shape Memory Alloy (Sma)mentioning
confidence: 99%
“…e SMA bolts with a superelastic property can provide moderate ED capacity for the connections [52]. e selfcentering connections using SMA bolts were tested by Chowdhury et al [47], Wang et al [53], and Fang et al [54,55] through experimental and numerical investigations. It was found that load capacity, initial stiffness, and ED Advances in Civil Engineering capacity were significantly related to the diameter, prestressed force, and length of SMA bolt.…”
Section: Connections Using Shape Memory Alloy (Sma)mentioning
confidence: 99%
“…Performance of steel braced frame reinforced with shape memory alloy wires was investigated by Varughese [50]. Chowdhury et al [51] present a new system for improving the seismic performance of post-tensioned self-centering connections using SMA angles or end plates with SMA bolts. Hosseini et al [52] conduct a comparative analysis between the structural performance and cost of using Fe-SMA vs. CFRP reinforcements for the post-tensioned strengthening of existing civil structures.…”
Section: Introductionmentioning
confidence: 99%